2016
DOI: 10.18632/oncotarget.9028
|View full text |Cite
|
Sign up to set email alerts
|

Similar cisplatin sensitivity of HPV-positive and -negative HNSCC cell lines

Abstract: Patients with HPV-positive head and neck squamous cell carcinoma (HNSCC) show better survival rates than those with HPV-negative HNSCC. While an enhanced radiosensitivity of HPV-positive tumors is clearly evident from single modality treatment, cisplatin is never administered as monotherapy and therefore its contribution to the enhanced cure rates of HPV-positive HNSCC is not known. Both cisplatin and radiotherapy can cause severe irreversible side effects and therefore various clinical studies are currently t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Collectively, our results demonstrated that ACHN‐shXPF cell presented impaired intra‐S‐phase checkpoint and more sub‐G1 population compare to that of ACHN‐shNC cell in response to cisplatin treatment, which together could explain the enhanced cisplatin sensitivity upon XPF knocking down. In support of this, previous studies have reported that loss of S‐phase arrest sensitizes cell to cisplatin‐induced DNA damage and cisplatin sensitive cells present more G2/M arrest than that of cisplatin resistant cells …”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Collectively, our results demonstrated that ACHN‐shXPF cell presented impaired intra‐S‐phase checkpoint and more sub‐G1 population compare to that of ACHN‐shNC cell in response to cisplatin treatment, which together could explain the enhanced cisplatin sensitivity upon XPF knocking down. In support of this, previous studies have reported that loss of S‐phase arrest sensitizes cell to cisplatin‐induced DNA damage and cisplatin sensitive cells present more G2/M arrest than that of cisplatin resistant cells …”
Section: Resultssupporting
confidence: 65%
“…In support of this, previous studies have reported that loss of S-phase arrest sensitizes cell to cisplatin-induced DNA damage 21 and cisplatin sensitive cells present more G2/M arrest than that of cisplatin resistant cells. 22…”
Section: Knocking Down Xpf Significantly Altered the Dna Damage Respomentioning
confidence: 99%
“…In published studies, different HPV-positive cell lines have shown considerable variations in sensitivity not only to irradiation 7,26,27 but also to cisplatin compared to HPV-negative cells 8,34 , and the same was observed in Figure 4. Cell cycle redistribution of HPV-negative (FaDu) and HPV-positive (2A3) cells after cisplatin (CDDP) treatment combined with single-dose (IR 2 Gy) (a) or fractionated irradiation (IR 3 × 2 Gy) (b).…”
Section: Discussionsupporting
confidence: 60%
“…In clinical practice, cisplatin adds a benefit to radiotherapy, with significant improvement of overall survival at five years in head and neck SCC patients 35,36 . It is known that cisplatin treatment increases the duration of S phase and arrests cells in the G 2 /M phase 8,34,[37][38][39] , which could contribute to radiosensitization. In the present study we share similar observations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, E6 has also been reported to impair HR while E7 had no effect (38) and nonisogenic comparisons of 1 HPV− and 2 HPV+HNSCC cell lines have suggested HPV-associated defects in NHEJ (39) or HR (39,40) or both (39). However, when larger cell line panels of HPV+ (n = 6) and HPV− HNSCC (n = 5) cell lines were compared, no difference in cisplatin sensitivity has been noted, which is a surrogate for HR efficiency (41). To deconvolve these observations on DSB repair, we measured all 3 major DSB repair pathways (NHEJ, HR, and MMEJ) in 3 separate assay systems and found consistent E7-mediated suppression of NHEJ and promotion of MMEJ, which matches human-level evidence in HPV-associated cancer genomes.…”
Section: Discussionmentioning
confidence: 99%